EFFECT OF CHANGES CUPPING THERAPY IN THE ELDERLY WITH JOINT PAIN RHEUMATOID ATRTRITIS (STUDY IN UPT PSLU JOMBANG) - Dedik Kurniawan; . Darsini; Marxis Uda (STIKES Insan Cendekia Medika Jombang, 2013)
Rheumatoid Arthritis is a disease that often strikes at the age of 35 years and over, which caused due to the reduced flexibility of cartilage pads and reduced production of synovial fluid, it can cause pain in the joints, to reduce pain can do cupping therapy. The purpose of this research is to analyze whether there’s change or not of joint pain changes with the method of cupping therapy. Research design used was pre-experimental with one group pretest-postest design method, the population was all elderly with rheumatoid arthritis i.e 24 respondents, large sample was 24 respondents, the method used in taking sample was by total sampling, the variable in this research were there’s independent varible that’s cupping therapy and the dependent variable was elderly with rheumatoid arthritis. The instrument in this research used observation sheet, the next being conducted data collecting then data processing which consist of editing, coding, scoring and tabulating, data analyzing used test of paired T-test. Before giving therapy there were 12 elderly with moderate pain, after giving therapy, moderate pain on elderly increased to15 it’s caused heavy pain which experienced by respondent reduced to be moderate pain. From the result of SPSS with test of t-test obtained that value of P = 0,000 which smaller than alpha (0,05), so H0 rejected H1 accepted. It means that there is an effect of giving cupping therapy to pain joint changes on elderly with rheumatoid arthritis. So it can be concluded there is a significant effect before and after given cupping therapy, from this result the researcher argues that effective cupping can relieve pain due to rheumatoid arthritis.